Generalised gamma spectrometry simulator for problems in nuclide identification. (December 2020) - Turner, A.; Wheldon, C.; Gilbert, M.R.; Packer, L.W.; Burns, J.; Kokalova Wheldon, Tz.; Freer, M.
Abstract: Improvements in Radio-Isotope IDentification (RIID) algorithms have always been a continuous research focus. However, significant developments in machine learning have recently sparked renewed interest. To provide a rapid development environment for this, a generalised gamma simulator has been built using the GEANT4 toolkit. This enables consideration of a diverse range of radiation sources and shielding scenarios. The simulator currently provides training data for the development of neural network based RIID models.